Evaluasi Pembelajaran Agama Islam di Universitas PGRI Argopuro Jember - Dahlan, Mukhtar Zaini; Jazuly, Ahmad; Suwargono, Trio; Masyitoh, Dewi (LPPM Universitas PGRI Argopuro Jember, 2024)
Evaluation of Islamic religious education is the main basis for understanding the extent to which the goals of Islamic religious education have been achieved, as well as for identifying areas of improvement that may be needed. Evaluation of PAI learning at PGRI Argopuro Jember University also has an impact on the quality of human resources produced by educational institutions. Students who have experienced a good PAI learning evaluation are expected to become agents of positive change in society, by implementing Islamic religious values ??in various aspects of life. The following are some of the urgency of evaluating PAI learning at PGRI Argopuro University, Jember, first to ensure the achievement of Islamic religious education goals. Second, Alignment of the PAI Curriculum. Third, improving the quality of learning. Fourth: Improvement of PAI learning strategies